PENGARUH EKSPEKTASI PENDAPATAN DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MOTIVASI BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Yugo, Ricardo; Asriati, Nuraini; Syahrudin, Husni (Universitas Tanjungpura, 2024)
The goal of this study is to determine how income expectations and entrepreneurial education affect the entrepreneurial motivation of FKIP UNTAN economics students. The study methodology used a quantitative approach and multiple linear regression. For this study, the data sources were students in the reg A and PPAPK classes for the academic years 2019, 2020, and 2021. The data were collected through a questionnaire. A total of 114 samples were included in the study. Researchers distributed questionnaires to the participants as part of their indirect communication approach to gather the necessary data. These questionnaires were administered using Google Forms. The researchers utilized a Likert scale as the survey method. The results of the study reveal the following: 1) Income expectations have a significant influence of 0.546 on entrepreneurial motivation, with a significance level ranging from 0.000 to 0.05. 2) Entrepreneurship education significantly impacts entrepreneurial motivation by 0.442, with a significance level of 0.000 to 0.05. 3) Simultaneously, entrepreneurial motivation is influenced by both income expectations and entrepreneurship education, with a calculated F-value of 26.416, which exceeds the critical F-table value of 3.08.